Implementation of Tajwid-Based Learning to Improve Students’ Qur’anic Reading Skills at SMKS YASPI Labuhan Deli - Nasution, Nur Nazwa (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the implementation of tajwid-based learning as an effort to improve students’ Qur’anic reading skills at SMKS YASPI Labuhan Deli. Tajwid learning plays a crucial role in ensuring accurate and rule-based Qur’anic recitation, thereby requiring effective instructional strategies. This research employs a qualitative descriptive method using observations, interviews, and documentation. The findings reveal that the implementation of tajwid learning involves demonstration techniques, repetitive practice (drill), and structured reading habituation. Teachers serve as models of correct recitation and facilitators who provide direct corrective feedback. The application of tajwid learning significantly enhances students’ accuracy in articulation (makhraj), recitation duration, and understanding of tajwid rules. Thus, the method is proven effective in improving students’ Qur’anic reading skills.